Uji Aktivitas Antioksidan Ekstrak Daun Senduduk (Melastoma Malabathricum L.) Berbasis Nades (Natural Deep Eutectic Solvent) dengan Metode Frap - Siti Melvy Susanti; Rizky Yulion Putra; Jelly Permatasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Senduduk plant (Melastoma Malabathricum L.) is known to contain bioactive compounds such as flavonoids, tannins and phenolics which have the potential as natural antioxidants. Excessive free radicals in the body can cause oxidative stress and trigger various degenerative diseases. Antioxidants play an important role in neutralizing free radicals. This study aims to evaluate the antioxidant activity of senduduk leaf extract based on NADES (Natural Deep Eutectic Solvent) using the FRAP (Ferric Reducing Antioxidant Power) method. The scope of the study includes the preparation of NADES using choline chloride and lactic acid with the molar ratios 1:1, 1:3 dan 1:5. Extraction was carried out using the Ultrasonic Assisted Extraction (UAE) method at temperatures of 30 ̊ C, 50 ̊ C and 70 ̊ C for 15, 30 and 60 minutes. The antioxidant activity was analyzed using UV-Vis spectrophotometry at a wavelength of 580 nm - 610 nm to measure the reduction of Fe3+ to Fe2+. The results showed that nearly all extracts had very strong antioxidant activity with IC50 values < 50 µg/ml. The best IC50 value was obtained at a NADES ratio of 1:1 temperature 70 ̊ C and 15 minute extraction time with a value of 2,37 µg/ml which is better than the Trolox standard 6,69 µg/mL. It can be concluded that NADES is effective as an environmentally friendly solvent for extracting antioxidant compounds from senduduk leaves.